PEMODELAN SPASIAL SISTEM INFORMASI GEOGRAFIS PENENTUAN JALUR EVAKUASI DI LERENG SELATAN GUNUNGAPI MERAPI DENGAN LUARAN ANDROID MOBILE APPLICATION - , CIPTA NUR ASA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research are to build a spatial database that contains information realted to the factors to determining evacuation route of Merapi Volcano by using Remote Sensing and Geographic Information Systems in Sleman regency. Determination of to find evacuation routes performed using Spatial Modeling of Geographic Information Systems namely Network Analyst. The making application of Merapi Evacuation Route on android smartphone is for dissemination of information effectively in order to reduce casulaties. The preparation of spatial database in this research is done by collecting information about rallying point location, the location of the refugee camp and the road network. The location rallying point was determined by calculating the vulnerability of the population number in Disaster Prone Areas of Merapi Volcano. The location of refugee camp is determined by the assseement criteria from a list refugee shelters published from Badan Penanggulangan Bencana Daerah and disaster occurence in 2010. The road network are used as the track of evacuation routes. The travel time used for the impedance value that is obtain by dividing the minimum design speed based the road class and lengths of each segment road. The application for smartphone android created from extraction of the data result to display via an application. Based on these research result, there are 89 evacution routes heading to six nearest location of the refugee camp. The evacution route with the fastest time travel is 3,57 minutes and the longest time was 48,36 minutes. The average travel times of the entire evacuation route to reaching location of the refugee camp is 13,59 minutes. Applications created with the Android Software Development Kit and Android Google Map API V2. The test results shown the value of performance evacuation route travel time on the field faster than the travel time from analysis results, and the Merapi Evacuation Route application works pretty good.